AN INSIGHT INTO SUBJECTIVE WELL-BEING: EVIDENCE FROM EUROPEAN SOCIAL SURVEY (Journal of European Studies (JES), 2017)
This study builds on European Social Survey for the year 2010 to estimate the well-being functions for 25,677 adults living across the continent. It is an attempt to explore the determinants of three major dimensions of well-being i.e., life evaluation, affect and eudaimonia. The paper contributes in the construction of three unique measures of subjective well-being. Also, it probes the societal and individual variables that may affect the levels of satisfaction in life. The proposed indices in the three dimensions of subjective well-being will help in the revival of policy to improve the overall condition of the populace. The simultaneous incorporation of three different measures augments the existent literature. Likewise, the choice of explanatory variables brings forward some interesting findings. For instance, education coupled with immigrant status increases life satisfaction but not necessarily emotional well-being. Similarly, policies aimed at the social inclusion of minorities carry a hugely positive influence on all the three stated measures of well-being.